2022
DOI: 10.1002/jcsm.13052
|View full text |Cite
|
Sign up to set email alerts
|

Acute skeletal muscle loss in SARS‐CoV‐2 infection contributes to poor clinical outcomes in COVID‐19 patients

Abstract: Background Chronic disease causes skeletal muscle loss that contributes to morbidity and mortality. There are limited data on the impact of dynamic muscle loss on clinical outcomes in COVID‐19. We hypothesized that acute COVID‐19‐related muscle loss (acute sarcopenia) is associated with adverse outcomes. Methods A retrospective analysis of a prospective clinical registry of COVID‐19 patients was performed in consecutive hospitalized patients with acute COVID‐19 ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Included articles were published between 2020 and 2022. Two studies reported data from both the first and second COVID-19 wave ( 41 , 42 ) and 4 studies investigated changes over time in body composition ( 43 , 44 , 45 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Included articles were published between 2020 and 2022. Two studies reported data from both the first and second COVID-19 wave ( 41 , 42 ) and 4 studies investigated changes over time in body composition ( 43 , 44 , 45 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between mortality and body composition abnormalities was investigated in 36 studies ( 4 , 37 , 40 , 42 , 43 , 46 , 47 , 48 , 50 , 53 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 70 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ) ( Figure 3 , Supplementary Table 4 ). Out of 24 of these studies, 12 showed that skeletal muscle mass assessed by either CT ( 43 , 47 , 50 , 56 , 61 , 77 , 78 , 80 , 86 , 88 ) or US ( 42 , 46 ) was negatively associated with in-hospital mortality and 30-day mortality ( 4 , 40 , 42 , 43 , 46 , 47 , 50 , 53 , 54 , 56 , 57 , 58 , 60 , 61 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in rats which were re-ambulated following 7 days of immobilization, soleus muscle regrowth was 20% greater in animals that had their rectal temperature raised to 41°C–41.5°C for 30 min every second day for 7 days compared to non-heated animals ( Selsby et al, 2007 ). Given that severe forms of COVID-19 are associated with muscle wasting ( Attaway et al, 2022 ), the findings of Selsby et al (2007) are highly relevant in the context of rehabilitation of those COVID-19 survivors who cannot exercise.…”
Section: Introductionmentioning
confidence: 99%